Biocoenotic Relationships of Saigas With Large Birds of Prey - Mikhail I. Shpigelman (Пернатые хищники и их охрана)
Conservation of biodiversity has recently become the most urgent task due to global anthropogenic transformation of the environment. Therefore, more and more attention is being paid to the role of species in biogeocenosis, their biocoenotic relationships and the assessment of ongoing changes. Due to the unprecedented growth of the Ural Saiga (Saiga tatarica) population, the study of ecology, behavior, and biocenotic relationships as factors affecting the structure of the ecosystem and, in particular, large birds of prey has become increasingly important.